INTERVENSI KOMBINASI PEMBERIAN SWEDISH BACK MASSAGE TECHNIQUE DAN MUROTAL AL-QUR’AN SURAH ARH-RAHMAN DI DESA KEMUTUG KIDUL KECAMATAN BATURRADEN KABUPATEN BANYUMAS - Friska Ambarwati; Ike Meiwati; Mariah Ulfah (Sekolah Tinggi Pariwisata Mataram, 2022)
The aging process in the elderly will cause a decrease in physical function to health conditions that make the elderly group susceptible to degenerative (non-communicable) diseases, one of which is abnormal blood pressure that occurs continuously. There are several non-pharmacological hypertension treatments, namely the Swedish back massage technique and murotal therapy where massage is carried out on the body combined with listening to the murrotal surah Ar - Rahman so that a relaxed feeling arises which will have an impact on lowering blood pressure. The purpose of this case study was to see the impact of the intervention of a combination of Swedish back massage techniques and murotal al-Qur'an Surah Ar - Rahman on reducing blood pressure in patients with hypertension. This research method uses a pre experimental design with a one group pretest-posttest approach. The results of the study found that the two subjects had the same gender, namely women, with subject 1 being 67 years old and subject 2 being 64 years old. The results of the case study showed a decrease in systolic and diastolic blood pressure in subject 1 by 9.3/4 mmHg and in subject 2 by 9.6/5.3 mmHg. Swedish therapy back massage techniques and murotal al-qur'an surah Ar - Rahman can lower blood pressure in patients with medical diagnoses hipertention.